Analysis of The Life Skills Level of PJKR STKIP Darussalam Cilacap Students in The Context of Positive Youth Development - Dian Imam Saefulah; Kusmiyati Kusmiyati; Andi Handoyo (Universitas Sebelas Maret, 2021)
The purpose of this study is to evaluate the degree of life skills acquired by PJKR STKIP Darussalam Cilacap pupils through physical exercise. Descriptive methodology combined with a survey technique was employed. All PJKR STKIP Darussalam Cilacap pupils who engaged in physical exercise made up the study's population. 50 respondents made up the sample, which was collected using the total sampling approach. The tool utilized was a life skills questionnaire that the researcher created. It included six parts: intrapersonal (increased attention, goal-setting, and emotional control); and interpersonal (honesty, collaboration, and respect). Data analysis used descriptive analysis as outlined in the form of percentages. The results showed that the level of life skills of PJKR STKIP Darussalam Cilacap students after participating in physical activity was in the category of